Unratified Treaties, Unilateral Declarations and Modus Vivendi: Circumstances to be considered to have Effect on State Parties - Mengesha, Zewdu (Bahir Dar University Journal of Law, 2022)
International law arises from the consent of states and state practice.The Vienna Convention on the Law of Treaties (VCLT, 1969) is anauthoritative international document regarding treaties between and amongstates. The VCLT provides rules and guidelines concerning the conclusion,entry into force, reservations, interpretation, amendments, modification,invalidity, termination and suspension of the operation of treaties. In order tohave binding effect, a treaty must fulfill the requirements provided under theVCLT. Some have argued that agreements that do not have a â€—normativeâ€˜character, laying down specific legal obligations rather than simply assertingpolitical positions, wishes or intentions, are not treaties. However, there is afascinating tendency in international law to cite, as authoritative and evenâ€•binding, acts that have not been legally completed, despite the fact that theformalities of completion are explicit requisites for their legality.In the decisions of the Permanent Court of International Justice (PCIJ)and the International Court of Justice (ICJ), it is possible to observe that unratified agreements, unilateral statements (acts) of states, modus vivendiand other unperfected treaties are creating legally binding obligations. TheEastern Greenland and Nuclear Tests cases provide poignant examples.1 Solong as such decisions have their own impact on countries, and it is commonto see that such treaties are used, it is important to study these court decisions.Nevertheless, concerns emanate from uncertainty over the conditions thatmust be fulfilled for unperfected agreements to have binding legal effect inthe eyes of international courts; in other words, the question of when, how,and why certain unperfected treaties should be treated as binding is animportant issue requiring clarification. In addition, it will provide adescription for legal advisors in the Ministry of Foreign Affairs trying topredict whether or not such undertakings may create binding legalobligations.In fact, international courts do give justifications as to why they basetheir decisions on unperfected treaties. Therefore an attempt will be made toanalyze these justifications. The author will look at the affirmative argumentsand the counter-arguments concerning why unperfected treaties should betreated as binding or not.